2006
DOI: 10.1111/j.1365-2621.2005.tb07172.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Glycated Soy 11S Glycinin

Abstract: EBO EBOAH AH AHAH AH sifying activity of the 11S-rich glycinin fraction with glycation (compared with control), especially at the early sifying activity of the 11S-rich glycinin fraction with glycation (compared with control), especially at the early sifying activity of the 11S-rich glycinin fraction with glycation (compared with control), especially at the early sifying activity of the 11S-rich glycinin fraction with glycation (compared with control), especially at the early sifying activity of the 11S-rich g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
51
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 54 publications
18
51
3
Order By: Relevance
“…The H 0 of SPI/G MRPs was lower than that of SPI/M MRPs, indicating that a higher degree of glycation resulted in decreased hydrophobicity, as DG of SPI/G MRPs was higher than that of SPI/M MRPs (Fig. 1), which is consistent with the finding of Achouri et al (2005) who suggested the decrease in hydrophobicity of 11S glycinin was connected with the increase in degree of glycation by glucose. Moreover, previous study also suggested that surface hydrophobic environment reduced more quickly as more polysaccharides were grafted with the protein (Mu et al 2010).…”
Section: Surface Hydrophobicity (H 0 )supporting
confidence: 81%
See 1 more Smart Citation
“…The H 0 of SPI/G MRPs was lower than that of SPI/M MRPs, indicating that a higher degree of glycation resulted in decreased hydrophobicity, as DG of SPI/G MRPs was higher than that of SPI/M MRPs (Fig. 1), which is consistent with the finding of Achouri et al (2005) who suggested the decrease in hydrophobicity of 11S glycinin was connected with the increase in degree of glycation by glucose. Moreover, previous study also suggested that surface hydrophobic environment reduced more quickly as more polysaccharides were grafted with the protein (Mu et al 2010).…”
Section: Surface Hydrophobicity (H 0 )supporting
confidence: 81%
“…It is possible that more sugars were accessible for interaction with ε-amino groups of lysine in protein as the increase of sugar concentrations, which would result in an improvement of the DG value. However, the glycation reaction reaches a saturation point due to the reduction of the number of ε-amino groups as the further increase in sugar concentrations (Achouri et al 2005), leading to slower increase in DG value. Therefore, sugar concentration at 8 % was carried out in the subsequent experiments.…”
Section: Degree Of Glycation (Dg)mentioning
confidence: 99%
“…The solubility profile was obtained by plotting the average protein solubility of triplicate samples versus pH. The procedure proposed by Waniska and Kinsella (1979) was followed for measuring foaming properties of SPI and CaCl 2 -11S with some modifications (Achouri et al, 2005). Emulsifying properties [emulsifying activity index (EAI) and emulsifying stability index (ESI)] were analyzed using the method of Pearce and Kinsella (1978).…”
Section: Functional Properties Of Control and Glycated Glycininmentioning
confidence: 99%
“…Improvement in functionality of soy proteins has also been achieved through hydrolysis and chemical modification (Achouri, Zhang, & Shiying, 1998;Qi, Hettiarachy, & Kalapathy, 1997;Wagner, Sorgentini, & Anon, 1996). It is also known that the Maillard reaction (glycation), carried out under dry state and well controlled conditions (temperature, relative humidity and time), is an adequate method for improving functionality of protein (Achouri, Boye, Yaylayan, & Yeboah, 2005;Chevalier, Chobert, Popineau, Nicolas, & Haertlé, 2001;Chobert, Gaudin, Dalgalarrondo, & Haertlé, 2006;Morgan, Leonil, Molle, & Bouhallab, 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial properties of protein have also been modified by a Maillard reaction between lysozyme and dextran 11 and chitosan and wheat gluten 14 . The Maillard reaction has also been shown to influence the functionality of soy protein 15,16 and egg proteins 17 .…”
Section: Introductionmentioning
confidence: 98%